Aoife Connolly. Performing the Pied-Noir Family: Constructing Narratives of Settler Memory and Identity in Literature and On-Screen. Lexington Books, 2020. - Tessa Nunn (Studies in 20th & 21st Century Literature, 2021)
Review of Aoife Connolly. Performing the Pied-Noir Family: Constructing Narratives of Settler Memory and Identity in Literature and On-Screen. Lexington Books, 2020. ix, 223 pp.
Keywords: Pied-noir; screen media; colonialism; gender; identity